KEKUATAN MENGIKAT PERJANJIAN NOMINEE DALAM PENGUASAAN HAK MILIK ATAS TANAH - I Wayan Werasmana Sancaya (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
Nominee Agreement or trustee is an agreement that use authority which is used the name of Indonesian residents name and the Indonesian residents give power of attorney to the foreigner to make them do an legal act towards their land. Nominee agreement often called with representation or borrowed name,depend on the letter of statement or power of attorney that made by both of the side, foreigner borrow names from Indonesian to be written as the land’s owner on the certificate, but then the Indonesian depend on the deed of declaration they have made ignore that the real owner of the land and its authorization do or represented to that foreigner. The validity and power of binding the nominee agreement is can’t be separated from clause 1320 and clause 1338 KUHPerdata. If the nominee agreement already notice ang fulfill the legitimate reguirement of the agreement based on clause 132 KUHPerdata and based on 1338 KUHPerdata, so that nominee agreement already have the binding power to every sides. Based on the principle of Pacta Sund Servanda, the agreement that is made by every sides, include nominee agreement has a binding power such as law for them who have made it.